The Galilean Crisis and Jesus Research Past and Present: A Response to Paula Fredriksen, Sarah Rollens, and Jens Schröter - Ferda, Tucker Samson (Journal for the study of the historical Jesus, 2022)
The author offers a grateful reply to his three respondents before clarifying a few matters and responding to queries. Nothing emerges that would require modifications to the main arguments of the book.